Neoadjuvant therapy of locally/regionally advanced melanoma. (July 2019) - Khunger, Arjun; Buchwald, Zachary S.; Lowe, Michael; Khan, Mohammad K.; Delman, Keith A.; Tarhini, Ahmad A.
Locally/regionally advanced melanoma confers a major challenge in terms of surgical and medical management. Surgical treatment carries the risks of surgical morbidities and potential complications that could be lasting. In addition, these patients continue to have a high risk of relapse and death despite the use of standard adjuvant therapy. Neoadjuvant therapy has the potential to significantly improve the clinical outcome of these patients, particularly in this era of newer and effective targeted and immunotherapeutic agents. Previous neoadjuvant studies tested chemotherapy with temozolomide where the clinical activity was limited. Biochemotherapy (BCT) was tested in two studies in the neoadjuvant setting and showed high tumor response rates; however, BCT was ultimately abandoned following its failure to demonstrate survival benefits in randomized trials of metastatic disease. Success of immunotherapy and targeted therapy in prolonging the lives of patients with metastatic melanoma generated considerable interest to investigate these novel strategies in the adjuvant and neoadjuvant settings. A number of neoadjuvant targeted and immunotherapy studies have been completed in melanoma to date and have yielded promising clinical activity. Given these encouraging results, a number of studies with other molecularly targeted and immunotherapeutic agents and their combinations are ongoing in the neoadjuvant setting; long-term outcome data are eagerly awaited. Such studies also provide access to biospecimens before and during therapy, allowing for the conduct of biomarker and mechanistic studies that may have a significant impact in guiding adjuvant therapy choices and drug development.